PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) DAN AKUNTABILITAS KINERJA RUMAH SAKIT - Abd. Rohman Taufiq (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
Standard Operational Procedure (SOP) is a guideline or reference for carrying out work duties in accordance with the functions and tools for evaluating hospital performance based on technical, administrative and procedural indicators in accordance with the work procedures concerned. The purpose of the SOP is to create commitments regarding hospital work units to realize good governance. SOP are not internal and external, because SOPs are used to measure the performance of public organizations relating to program accuracy and time. In addition, SOP is used to assess the performance of public organizations in the form of responsiveness, responsibility, and accountability of hospital performance. The results of the study show that not all hospital work units have an SOP, because each unit of the public service unit of the hospital has an SOP as a reference in acting, so that the performance accountability of hospital agencies can be evaluated and measured.